Universitas, Negara, dan Masyarakat Indonesia: Implementasi Paradigma Modernisasi di Era Orde Baru - Hanneman Samuel (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
More than just a slogan, modernization is a complex of political knowledge. Scientific studies intertwine with development strategy in such a way that modernization theories became means of communications as well as means of orientations. This is exemplified during the New Order era: Indonesian academic intellectuals justify their support for the New Order government on scientific bases. Based on the use of library research, there are four fields upon which intersections between the interests of the New Order government and the interests of academic intellectuals have rested. The first is the systemic integration of Indonesian society. The second is New Order era as the beginning of development. The third concerns with technocratisation of development. The fourth concerns with the dilemma of poverty.